THE USE OF FLASHCARDS TEACHING STRATEGY IN RECALLING ENGLISH VOCABULARY - Ida Ayu Made Yuni Andari; Ida Bagus Alit Arta Wiguna; Ni Made Arini (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
This research focuses on using the strategy of learning flashcards to recall English vocabulary, and students in the game group learn to recall English vocabulary types through learning flashcards. Find out what kind of vocabulary students in the English language recall playgroup through the flashcard learning strategy, analyze the process of recalling English vocabulary using the flashcard learning strategy. This study uses a qualitative method. The data source for this study will be conducted in Hooray Denpasar. Express oral data as written data by taking notes. One month of direct observation can be used to learn more about the process of using flashcards to recall English. The research methods used in this study are divided into three points. The first point is how data is collected, the second point is how data is analyzed, and the third is how data analysis is presented. This research led to the use of flashcards teaching strategy in English vocabulary recalling school. This strategy is very effective and very helpful for students to accept classroom learning.